The influence of using Instagram @dishubsurakarta on fulfilling followers' information needs - Anisa Fitriyani; Budi Santoso (Institute of Computer Science (IOCS), 2024)
The use of Instagram social media has been utilized by government agency public relations, including the Surakarta Transportation Service, in an effort to meet the public's information needs. This research aims to determine the influence of Intagram @dishubsurakarta on fulfilling the information needs of its followers. This research uses quantitative methodology by distributing questionnaires to followers of Instagram @dishubsurakarta online. This research uses the Uses & Gratification Needs theory of Herbert Blumer and Elihu Katz. The population of this research are followers of the @dishubsurakarta account. The sample from this research consisted of 100 respondents taken using probability sampling techniques. The data analysis techniques used in this research are descriptive tests, validity tests, reliability tests, normality tests, paired t tests and simple linear regression. The research results based on the t hypothesis test, simple linear regression test, coefficient of determination, provide results that the social media use variable (X) has a significant positive effect on the information needs variable (Y).